The Implementation of the POPMAR (Policy, Organising, Planning and Implementing, Measuring Performance, Audit and Reviewing) Model in Occupational Health and Safety Risk Management in an Indonesian Batik Company - Fandita Tonyka Maharani; Zena Lynch (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: In 2009, UNESCO declared Batik Indonesia as an Intangible Cultural Heritage of Humanity. This study examines the occupational health and safety hazards and risks that arise in a Batik company based on a case example of a Batik company in Surakarta, Indonesia. In Indonesia, Batik is categorized as traditional attire. Two kinds of Batik are produced - Batik tulis (traditionally handcrafted) and Batik printing, which uses specific printing tools. The UK Health Safety Executive (HSE) risk assessment framework is referred to in this study, which consists of: hazard identification, population exposure, risk evaluation, precaution development, recording findings, and regular appraisal of systems. Methods: Both observation and interviews (of workers) at the Batik company were utilized for this study as well as an independent risk assessment. Results: The findings highlighted physical, ergonomic, chemical, mechanical, and biological hazards, originating from the materials, tools, and working methods utilized in the batik production. Conclusion: Many of the issues highlighted by this study can be addressed via in-depth risk assessment, using the POPMAR model to frame the activities. This approach can create a positive pathway, leading to a continuous cycle of improvement which puts the workers’ health at the forefront of the business activities.Keywords: Batik, workers, hazard identification, HSE Model, risk management